Temperature and Patterns of Occurrence and Abundance of Key Copepod Taxa in the Northeast Pacific - Ashlock, Lauren; García-Reyes, Marisol; Gentemann, Chelle; Batten, Sonia; Sydeman, William (Frontiers in Marine Science, 2021)
The Northeast Pacific is a highly heterogeneous and productive ecosystem, yet it is vulnerable to climate change and extreme events such as marine heat waves. Recent heat wave induced die-offs of fish, marine mammals, and seabirds in the Gulf of Alaska were associated with the loss of large, lipid-rich copepods, which are a vital food resource for forage fishes. The critical and temperature sensitive role of copepods in this ecosystem motivates our investigation into the impacts of temperature on copepod occurrence, abundance, and phenology. Here, we pair long term in situ copepod data from Continuous Plankton Recorder surveys with satellite temperature data to determine the influence of water temperature on three key copepod taxa: Neocalanus plumchrus, Calanus pacificus, and Oithona spp. Through the use of linear models and thermal threshold methods, we demonstrate that N. plumchrus is most vulnerable to warming and future marine heat waves in this region. Linear models demonstrate that N. plumchrus abundance is negatively related to temperature, and thermal threshold methods reveal that N. plumchrus has an upper thermal threshold of 11.5°C for occurrence, and 10.5°C for abundance. Additionally, examining N. plumchrus abundance before and during the 2014-2016 marine heat wave demonstrates reduced species abundance during past warming events. Oithona spp. and C. pacificus appear to be less vulnerable to warm temperatures. However, their presence will not be sufficient to supplement the loss of the larger-bodied and lipid-rich N. plumchrus. Our findings demonstrate the power of using long-term in situ data to determine thermal tolerances, and suggest the need to further examine the potential resilience of N. plumchrus to climate change.